PROTOGNATHODUS (CONODONTA) AND ITS POTENTIAL AS A TOOL FOR DEFINING THE DEVONIAN/CARBONIFEROUS BOUNDARY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
The current definition of the Devonian/Carboniferous boundary is the first occurrence of the conodont Siphonodella sulcata. Due to difficulties in identification of the early siphonodellids, such as S. praesulcata and S. sulcata, investigation of Protognathodus which enters in the latest Devonian and extends into the Mississippian, was undertaken to determine use as a better indicator of the base of the Carboniferous. During the D/C boundary interval, Protognathus is represented by four species: Pr. meischneri, Pr. collinsoni, Pr. kockeli and Pr. kuehni.Although Pr. kockeli can be abundant in boundary interval sections, none of the four Protognathodus species has a high potential as a tool for redefining the D/C boundary, based on regional variation in first occurrence data, restricted stratigraphic ranges and global distribution, poorly understood facies occurrences, as well as general rarity of the taxa.
Keywords: Biostratigraphy; Taxonomy; Devonian/Carboniferous Boundary; Conodonts; Protognathodus